Overseas Smart City Short Course of Airlangga and International Community Service: The Role of Science and Technology Towards Smart City - Fitriani, Nurina; Fatmawati, Fatmawati; Samiaji, Tabina Arqika; Dianbudiyanto, Wahid; Hutama, Dio Alif; Kuncoro, Eko Prasetyo (Journal of Sustainability Perspectives, 2024)
The smart city concept emerged as an alternative solution to overcome the negative impacts of urbanization in big cities, based on the concept of sustainable development. A smart city is a city that can utilize human resources, social capital, and modern telecommunications infrastructure to achieve sustainable economic growth and high quality of life through wise management of resources by the government based on community participation. Jombang has not been managed optimally due to a lack of digital exposure and promotion. Based on these problems, the Faculty of Science and Technology, Airlangga University will organize an international community service program in Jombang to introduce culture and tourism in Jombang to the world through international students and transfer knowledge regarding the application of smart tourism to increase tourism promotion in Jombang. This community service program was carried out together with international students who will first be given an introduction and knowledge of the smart city concept and its application at Universitas Airlangga and the City of Surabaya through a short course. Then the students will be invited to visit the tourist and cultural village in Jombang to transfer knowledge to the local community regarding the application of the smart tourism concept to promote tourism potential in Jombang.